Formulation of a Moisturising Hand Cream Using Shea Butter, Sodium Alginate, and Sweet Almond Oil: A Review - Samidha Singh; Kalash Upadhyay; Sarika Shrivastava; Jitendra Banweer (Asian Journal of Pharmaceutical Research and Development, 2025)
Objective: This study aimed to formulate and evaluate a moisturising hand cream using natural ingredients—shea butter, sodium alginate, and sweet almond oil—to address skin dryness caused by frequent exposure to water, chemicals, or harsh environments. Significance: With rising interest in clean-label and plant-based skincare, the project explores the potential of naturally derived ingredients as effective, skin-friendly alternatives to synthetic components in hand care formulations. Methods: The hand cream was prepared using the fusion method, which involves heating the oil and aqueous phases separately, then blending them with continuous stirring to form a stable emulsion. Shea butter and sweet almond oil composed the oil phase, while sodium alginate was dissolved in the aqueous phase. The two were combined at equal temperatures and allowed to cool while mixing, forming a smooth, Homogenous cream without synthetic emulsifiers. Results: The final formulation had a creamy, non-greasy texture that spread easily and was quickly absorbed. The pH ranged from 5.6 to 6.1, aligning with skin compatibility. Spreadability and washability were favorable, and stability studies over four weeks showed no significant changes in texture, color, or pH under ambient and accelerated conditions. Conclusions: The fusion method successfully produced a stable, effective hand cream using only plant-based ingredients. The formulation met essential quality and performance parameters, highlighting the potential of natural components in developing safe, functional, and sustainable skincare products.